Razão e proporção no ensino básico - Sousa, Raimundo Neto de (2023)
This work aims to present a proposal for teaching ratio and proportion in high school, with emphasis on the development of students' logical-mathematical reasoning. Ratio and proportion are fundamental concepts of Mathematics that have application in several areas of knowledge, in addition to being essential for the understanding of more advanced subjects, such as algebra and geometry. The teaching of reason and proportion is often carried out mechanically and out of context, making it difficult for students to assimilate and apply the concepts. From this perspective, we propose an approach that seeks to stimulate critical thinking and problem-solving skills, aiming at learning significant. The proposal consists of a didactic sequence composed of different stages, which begins with the contextualization of the concepts of ratio and proportion through problem situations of the students' daily lives. These situations provide a favorable environment for students to perceive the presence of these concepts in their daily lives, stimulating their interest and motivating their active participation in the learning process. Next, students are challenged to carry out investigations, exploring different strategies to solve problems involving ratio and proportion. Emphasis is placed on understanding the procedures adopted, encouraging the search for justifications and the exchange of ideas among students. Collaborative problem solving is also encouraged, promoting interaction and the collective construction of knowledge. In addition, the use of technological resources, such as simulation software and cell phone applications, is proposed to expand the possibilities for exploring the concepts. These tools offer an interactive and visually attractive environment that favors understanding and experimenting with the concepts of ratio and proportion. Assessment is conceived as a continuous and formative process, aimed at identifying difficulties and student progress. Different instruments are used, such as individual and group activities, production of reports and presentations, as well as systematic observation of students during classes. The assessment also seeks to value the learning process and the development of logical-mathematical reasoning skills. It is hoped that the proposal presented in this work will contribute to a more dynamic and meaningful approach to the teaching of ratio and proportion in Teaching Average. Through this approach, students will have the opportunity to develop essential skills for their comprehensive education, such as the ability to solve problems, work in teams and relate mathematical concepts to real situations. The expected result is more effective and lasting learning, which prepares students for the challenges of the contemporary world, both academically and in practical life.